Fairtrade, Food Security and Globalization: Building Alternative Food Systems - Martin Calisto Friant (Íconos)
This article examines the politics and practices of Fairtrade certification in order to assess whether this alternative trading system could contribute to innovative solutions for global food security. The analysis begins by assessing the main challenges and problems characterizing the contemporary global food system. It then explores the history, vision and certification standards of the Fairtrade label. In the third section, the results of the impact studies of Fairtrade certification on producer livelihoods are discussed, analyzing the various strengths and weaknesses. Finally the article analyzes whether, and how, the Fairtrade system could positively contribute to improving global food security. To conclude this paper argues that the greatest strength of Fairtrate is not the certification mechanism itself but rather the social and environmental principles it represents. Fairtrade standards could serve to inform broader international policies, which could lead to a sustainable transformation of the global food system.